Insight Into Dynamics of Gut Microbial Community of Broilers Fed With Fructooligosaccharides Supplemented Low Calcium and Phosphorus Diets - Kumar, Sanjay; Shang, Yue; Kim, Woo Kyun (Frontiers in Veterinary Science, 2019)
The effect of low calcium (Ca) and available phosphorus (aP) diet and prebiotic fructooligosaccharides (FOS) supplementation on ileum and cecum microbiota of broiler chickens was investigated in a three-wk trial. Three dietary treatments were randomly assigned to four replicate cages of five birds each, including: positive control (PC), a wheat-corn-soybean meal-based diet according to NRC requirement; negative control (NC), as PC with 0.2% reduced Ca and aP; and NC+FOS, as NC supplemented with 0.5% of FOS. Ileal and cecal digesta from each replicate (n =12) were sampled on d 21. DNA was extracted for the amplification of V4 region of bacterial 16S rRNA genes and subjected to Illumina sequencing. Bioinformatics analyses were performed using QIIME. Statistical difference was determined by 2-way ANOVA and Permanova. On average, 24,216 sequence reads per sample were generated resulting in 800 and 1,280 operational taxonomic units in the ileal and cecal digesta, respectively. Species richness and diversity, number of observed species and abundances of several phyla, including Cyanobacteria, Firmicutes and Proteobacteria were different (P < 0.0001) between ileal and cecal digesta. Treatment effect on ß-diversity was different (P < 0.05) in the ileum but not in the cecum. In the ileal digesta, Salinibacterium and Lysobacter were positively correlated to PC but negatively to NC and NC+FOS. Blautia, Faecalibacterium and Pseudomonas were positively correlated to NC, whereas Pseudonocardia and CF231 were negatively correlated. Lactobacillus and Escherichia were found to be more abundant in NC+FOS. In the cecum digesta, species richness, phylogenetic diversity and the number of observed species were higher (P < 0.05) in PC compared to NC+FOS. Butyrivibrio and Allobaculum were positively correlated to PC; Clostridium and Anaerotruncus were positively correlated to NC+FOS, whereas negatively correlated to PC and NC. Data showed that the cecum microbiota was richer than that of the ileum. The NC and NC+FOS diets altered the ileum microbiota composition and the richness of the cecal content. The study concludes that dietary Ca and aP level and FOS supplementation modulate ileal microbiota of the broiler chickens.